STRATEGI GURU DALAM MENINGKATKAN HASIL BELAJAR PESERTA DIDIK MELALUI METODE PROBLEM BASED LEARNING PADA PEMBELAJARAN PAI DI SMPN 2 JOGOROTO JOMBANG - Nabila Kumalasari; Didin Sirojudin (JURNAL ILMIAH PENELITIAN MAHASISWA, 2025)
This study aims to examine teacher strategies in implementing the Problem-Based Learning (PBL) method in Islamic Religious Education (PAI) learning, the implementation of the PBL method, and the obstacles and solutions in improving student learning outcomes at SMPN 2 Jogoroto Jombang. The research method used was descriptive qualitative, with data collection techniques through observation, interviews, and documentation. The results indicate that teacher strategies in implementing the PBL method include careful planning, student-centered implementation, and comprehensive evaluation. The implementation of the PBL method has proven effective in improving student learning outcomes, both in cognitive, affective, and psychomotor aspects. However, several obstacles remain, such as time constraints, heterogeneity of student abilities, and a lack of supporting resources. Possible solutions include improving teacher competency, providing adequate learning facilities, and optimizing the role of parents in the learning process. Thus, it is hoped that student learning outcomes can be optimally improved.